2021
DOI: 10.3390/nu14010191
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gut Microbiota on the Beneficial Effects of Ketogenic Diets

Abstract: The ketogenic diet is a dietary regime focused on strongly reducing carbohydrate intake and increasing fat intake; leading to a state of ketosis. The ketogenic diet has gained much popularity over the years due to its effects on promoting weight loss, increasing insulin sensitivity and reducing dyslipidaemia. All these factors play a crucial role in the development of cardio-metabolic diseases; one of the greatest health challenges of the time. Moreover, the ketogenic diet has been known to reduce (epileptic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 79 publications
1
45
1
1
Order By: Relevance
“…Another mechanism, increasingly frequently mentioned in publications, is the effect of the ketogenic diet on the prevention and treatment of neurological diseases (including neurodegenerative ones) through a change of intestinal microbiota [ 82 ]. This results from a possible influence of intestinal dysbiosis on the development of such diseases, while on the other hand, it is known that a ketogenic diet significantly affects the remodelling of the intestinal microbiota [ 83 ]. Thus, increasingly, the subject of the potential indirect favourable effect of the ketogenic diet on neurological diseases through the modulation of intestinal microbiota is discussed.…”
Section: The Range and Mechanisms Of The Ketogenic Diet Effect In Neu...mentioning
confidence: 99%
“…Another mechanism, increasingly frequently mentioned in publications, is the effect of the ketogenic diet on the prevention and treatment of neurological diseases (including neurodegenerative ones) through a change of intestinal microbiota [ 82 ]. This results from a possible influence of intestinal dysbiosis on the development of such diseases, while on the other hand, it is known that a ketogenic diet significantly affects the remodelling of the intestinal microbiota [ 83 ]. Thus, increasingly, the subject of the potential indirect favourable effect of the ketogenic diet on neurological diseases through the modulation of intestinal microbiota is discussed.…”
Section: The Range and Mechanisms Of The Ketogenic Diet Effect In Neu...mentioning
confidence: 99%
“…These observations are very similar to prior work showing that the KD can dramatically increase A. muciniphila ( 40 , 41 ). Although not the focus of the present study, A. muciniphila is associated with improved metabolic health in both animal and human studies ( 42 44 ). This species could be an interesting focus of future experiments designed to determine if the changes in the microbiome impacted the behavioral outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Its potential effects on cancer immune therapy have just begun to emerge in an animal model 73 . The exact mechanism by which a KD exerts potential anticancer activities remains unknown, but recent evidence points toward a crucial role for the gut microbiota 74,75 . An interesting study in both mice and humans found that a KD led to decreased fecal Bifidobacterium abundance, which led to lower levels of intestinal and visceral fat proinflammatory T H 17 cells 76 .…”
Section: Prebiotic and Probiotic And Dietary Supplements In Cancer-di...mentioning
confidence: 99%
“…An RCT to investigate the effects of a 2-month KD followed by a 2-month low-calorie diet concluded that the KD resulted in a beneficially altered gut microbiota composition, that is, reduced relative abundances of Serratia , Erwinia , and Citrobacter and increased relative abundances of Oscillospira and Butyricimonas. 78 However, overall changes in gut microbiome composition induced by KD in the literature are very inconsistent, suggesting need for more well-designed studies 74,75 …”
Section: Prebiotic and Probiotic And Dietary Supplements In Cancer-di...mentioning
confidence: 99%